"Oh Events" for the Professor: Studies and Stories of Religious Studies Abroad. (January 2015) - Barbour, John D.
Abstract This response explains three ways in which the preceding essays are a significant contribution to the study of study abroad, explores three additional issues, and makes three suggestions for future work on religious studies and study abroad. This response is published alongside of six other essays, comprising a special section of the journal (see Teaching Theology and Religion 18:1, January 2015).